Carbon supported metal fluoride and its use in electrochemical nitrite sensing
Patent Information
- Application Number
- CN202311160787.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-09-08
AI Technical Summary
[0004]针对当前亚硝酸盐电化学监测使用的电极材料存在的单一材料导电性差,对亚硝酸盐的催化活性不高,传感器灵敏度有限等缺点,本发明提供一种新型的电极修饰材料碳载金属氟化物
[0016](1)本发明提供的碳载金属氟化物是一种新颖的电极修饰材料,碳掺杂解决了金属氟化物弱导电性的缺陷。即解决了当前亚硝酸盐电化学监测使用的单一电极材料存在的导电性差,对亚硝酸盐的催化活性不高的问题。碳载金属氟化物的高催化活性可以更加灵敏高效的催化氧化亚硝酸根离子。在亚硝酸盐的电催化氧化反应中具有高催化活性和良好稳定性,以其修饰的工作电极作为传感元件具有电化学亚硝酸盐传感的优异性能。
Smart Images

Figure CN117434122B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode materials technology, and in particular to a carbon-supported metal fluoride and its application in electrochemical nitrite sensing. Background Technology
[0002] Nitrites are widely used in the food industry as food additives due to their coloring, antibacterial, and food preservation properties. However, excessive nitrites can be highly toxic, affecting the oxygen-carrying function of hemoglobin in the human body. They can also combine with amines produced from protein hydrolysis to synthesize N-nitrosamines, which are carcinogenic, thus impacting human health. Therefore, achieving sensitive, efficient, and rapid detection of nitrites in food is of great significance for protecting human health.
[0003] Existing methods for nitrite detection mainly include diazo coupling colorimetry, ion chromatography, and spectrophotometry. These methods typically require complex sample pretreatment and are time-consuming and complex to operate. In contrast, electrochemical sensors offer advantages such as high sensitivity, fast detection speed, ease of operation, and low cost. To improve the electrocatalytic properties of nitrite sensors, various nanomaterial-modified electrodes, such as metals, metal oxides, and carbon nanomaterials, have been widely used in nitrite detection. However, these materials still suffer from drawbacks such as poor conductivity of individual materials, low catalytic activity for nitrite, and limited sensor sensitivity. Summary of the Invention
[0004] To address the shortcomings of current electrode materials used in nitrite electrochemical monitoring, such as poor conductivity of single materials, low catalytic activity against nitrite, and limited sensor sensitivity, this invention provides a novel electrode modification material: carbon-supported metal fluoride. The working electrode made from this carbon-supported metal fluoride material can more sensitively and efficiently catalyze the oxidation of nitrite ions.
[0005] The carbon-supported metal fluoride provided by this invention is prepared by the following method:
[0006] Step 1: Add the organic carbon source, metal salt, and fluoropolymer to a solvent and mix thoroughly to form a sol. The solvent is selected from one of the following: 10% boric acid, deionized water, methanol, ethanol, and phenol.
[0007] Step 2: Freeze-dry the sol at a temperature of -10 to -30°C for 24 to 48 hours to obtain a blocky foam with internal pores.
[0008] Step 3: Place the block foam in an inert atmosphere at a gas flow rate of 20–50 ml / min. -1Carbonization was carried out by constant calcination at 600℃ for 2-4 hours, followed by cooling and grinding to obtain a black powdery carbon-supported metal fluoride.
[0009] Preferably, the organic carbon source is solara or polyvinyl alcohol.
[0010] Preferably, the metal salt is selected from one of cerium salts, iron salts, cobalt salts, calcium salts, magnesium salts, and vanadium salts. More preferably, the metal salt is one of cerium trichloride, ferric chloride, cobalt chloride, calcium chloride, magnesium chloride, or vanadium chloride.
[0011] Preferably, the fluoropolymer is a concentrated dispersion of polytetrafluoroethylene.
[0012] Preferably, the mass ratio of the organic carbon source, metal salt, and fluoropolymer is 1:(0.05-0.3):(1-4). The mass-volume ratio of the organic carbon source and the solvent is (1-3) g:(4-8) mL.
[0013] The application of the carbon-supported metal fluoride prepared by the above method in electrochemical nitrite sensing: A dispersion of the carbon-supported metal fluoride, ethanol, and Nafion solution is drop-coated onto the surface of a glassy carbon electrode to form a working electrode, with a platinum wire electrode as the counter electrode and a saturated silver chloride electrode as the reference electrode. Sodium nitrite solution is added to a buffer solution, and the peak current of the oxidation peak of nitrite ions on the prepared working electrode is detected using differential pulse voltammetry. A standard curve is established based on the peak current intensity of the oxidation peak and the concentration of nitrite ions. The concentration of nitrite ions in the sample can be obtained from the standard curve.
[0014] Preferably, the buffer solution is a 0.1M phosphate buffer solution with a pH of 5.0–9.0. The differential pulse voltammetry has an amplitude of 50 mV, a pulse width of 0.2 s, and a pulse period of 0.5 s.
[0015] Compared with the prior art, the advantages of the present invention are:
[0016] (1) The carbon-supported metal fluoride provided by this invention is a novel electrode modification material. Carbon doping solves the defect of weak conductivity in metal fluorides. That is, it solves the problems of poor conductivity and low catalytic activity for nitrite in the single electrode materials currently used for electrochemical monitoring of nitrite. The high catalytic activity of the carbon-supported metal fluoride can more sensitively and efficiently catalyze the oxidation of nitrite ions. It has high catalytic activity and good stability in the electrocatalytic oxidation reaction of nitrite, and the working electrode modified with it has excellent performance in electrochemical nitrite sensing when used as a sensing element.
[0017] (2) The working electrode based on carbon-supported metal fluoride of the present invention has high sensitivity, wide detection range, fast response speed, strong anti-interference ability and high stability, and has strong practicality.
[0018] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description
[0019] Figure 1 SEM images of CeF3 / C.
[0020] Figure 2 XRD pattern of CeF3 / C.
[0021] Figure 3 (a) The differential pulse voltammetry response curves after adding different concentrations of nitrite ions to 0.1M phosphate buffer (pH 7.0) with CeF3 / C as the working electrode, platinum wire electrode as the counter electrode, and saturated silver chloride electrode as the reference electrode; (b) The linear fitting curve of peak current versus nitrite ion concentration.
[0022] Figure 4 The results show the anti-interference performance of CeF3 / C for the detection of nitrite ion concentration.
[0023] Figure 5 The results show the stability test performance of CeF3 / C for detecting nitrite ion concentration. Detailed Implementation
[0024] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0025] Example 1
[0026] Preparation of carbon-supported metal fluoride CeF3 / C: 1 g of solara gel, 0.15 g of cerium trichloride heptahydrate, 2 g of concentrated polytetrafluoroethylene dispersion, and 5 mL of 10% boric acid solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and then in the center of a tube furnace, where it was incubated at 40 mL / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cerium fluoride, denoted as CeF3 / C.
[0027] Figure 1The image shows a SEM image of CeF3 / C, which indicates that CeF3 / C consists of nanoparticles with a diameter of approximately 50 nm.
[0028] Figure 2 The image shows the XRD pattern of CeF3 / C. The two broad peaks at 25.5° and 43.4° correspond to standard card JCPDS 41-1487, representing amorphous carbon. The remaining sharp peaks correspond to standard card JCPDS 08-0045, representing CeF3.
[0029] The method for applying CeF3 / C to the electrochemical detection of nitrite involves preparing a dispersion of CeF3 / C with ethanol and Nafion solution, which is then drop-coated onto the surface of a glassy carbon electrode as the working electrode. A platinum wire electrode serves as the counter electrode, a saturated silver chloride electrode as the reference electrode, and 0.1M phosphate buffer (pH 7.0) is used as the electrolyte. Figure 3 As shown in (a), sodium nitrite solution with a concentration of 0–1500 μL was added to the electrolyte, and the peak current of the prepared working electrode for the catalytic oxidation of nitrite ions was detected using the differential pulse voltammetry method; Figure 3 As shown in (b), a standard curve was established using the peak current intensity of the oxidation peak versus the nitrite ion concentration. Experimental results show that the CeF3 / C working electrode prepared by the method of this invention has a sensitivity of 854.52 μA mM for the electrochemical detection of nitrite ions. -1 cm -2 The detection range is 1–1500 μM, and the detection limit is 0.47 μM when the signal / noise ratio is 3 (S / N = 3).
[0030] Example 2
[0031] Preparation of carbon-supported metal fluoride FeF3 / C: 1 g of solara gel, 0.12 g of anhydrous ferric chloride, 3 g of concentrated polytetrafluoroethylene dispersion, and 4 mL of methanol solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and then in the center of a tube furnace, where it was incubated in 40 mL of water for 1 minute. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported iron fluoride, denoted as FeF3 / C.
[0032] The method for electrochemical nitrite detection using FeF3 / C is as follows: the testing procedure is the same as in Example 1. Experimental results show that the FeF3 / C working electrode prepared by the method of this invention has a sensitivity of 810.63 μM for electrochemical detection of nitrite ions. -1 cm -2The detection range is 2.5–1370 μM, and the detection limit is 0.82 μM when the signal / noise ratio is 3 (S / N = 3).
[0033] Example 3
[0034] Preparation of carbon-supported metal fluoride CoF2 / C: 1 g of Solar gum, 0.15 g of cobalt chloride hexahydrate, 2 g of concentrated polytetrafluoroethylene dispersion, and 5 mL of deionized water were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and placed in the center of a tube furnace, then incubated in 40 mL / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cobalt fluoride, denoted as CoF2 / C.
[0035] The CoF2 / C electrode was used for electrochemical nitrite detection: the testing method was the same as in Example 1. Experimental results showed that the CoF2 / C working electrode prepared by the method of this invention had a sensitivity of 779.02 μAmM for electrochemical detection of nitrite ions. -1 cm -2 The detection range is 3–1310 μM, and the detection limit is 1.15 μM when the signal / noise ratio is 3 (S / N = 3).
[0036] Example 4
[0037] Preparation of carbon-supported metal fluoride CaF2 / C: 1 g of solara gel, 0.15 g of cobalt chloride, 3 g of concentrated polytetrafluoroethylene dispersion, and 4 mL of ethanol solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and placed in the center of a tube furnace, then incubated in 40 mL of water for 1 minute. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cobalt fluoride, denoted as CoF2 / C.
[0038] The CaF2 / C electrode was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the CoF2 / C working electrode prepared by the method of this invention had a sensitivity of 750.83 μA mM for electrochemical detection of nitrite ions. -1 cm -2 The detection range is 5–1300 μM, and the detection limit is 1.60 μM when the signal / noise ratio is 3 (S / N = 3).
[0039] Example 5
[0040] Preparation of carbon-supported metal fluoride MgF2 / C: 2g polyvinyl alcohol, 0.3g magnesium chloride, 4g concentrated polytetrafluoroethylene dispersion, and 5mL 5% phenol solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 hours to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and then in the center of a tube furnace, where it was incubated in 40ml / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported magnesium fluoride, denoted as MgF2 / C.
[0041] The MgF2 / C electrode was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the MgF2 / C working electrode prepared by the method of this invention had a sensitivity of 736.55 μM for electrochemical detection of nitrite ions. -1 cm -2 The detection range is 5.7–1263 μM, and the detection limit is 2.21 μM when the signal / noise ratio is 3 (S / N = 3).
[0042] Example 6
[0043] Preparation of carbon-supported metal fluoride VF3 / C: 1.5 g polyvinyl alcohol, 0.2 g vanadium chloride, 4 g concentrated polytetrafluoroethylene dispersion, and 5 mL 10% boric acid solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and placed in the center of a tube furnace, then incubated at 40 mL / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 600℃ and held for 4 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cobalt fluoride, denoted as VF3 / C.
[0044] The VF3 / C electrode was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the VF3 / C working electrode prepared by the method of this invention had a sensitivity of 719.35 μA mM for electrochemical detection of nitrite ions. -1 cm -2 The detection range is 8–1270 μM, and the detection limit is 3.06 μM when the signal / noise ratio is 3 (S / N = 3).
[0045] Comparative Example 1
[0046] Preparation of the metal fluoride CeF3: 1 g of solara gel, 0.15 g of cerium trichloride heptahydrate, 2 g of concentrated polytetrafluoroethylene dispersion, and 5 mL of 10% boric acid solution were uniformly mixed to form a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and placed in the center of a muffle furnace, incubated at 5 °C for 5 min. -1 The temperature was raised to 600℃ and held for 2 hours, then allowed to cool naturally. The resulting substance was ground into powder to obtain cerium fluoride, denoted as CeF3.
[0047] CeF3 was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the CeF3 working electrode prepared by the method of this invention had a sensitivity of 264.19 μA mM for electrochemical detection of nitrite ions. -1 cm -2 The detection range is 47–300 μM, and the detection limit is 40 μM when the signal / noise ratio is 3 (S / N = 3).
[0048] The detection results of nitrite ions in Comparative Example 1 and Example 1 show that single metal fluoride materials have weak conductivity and low catalytic activity. The carbon doping of this invention overcomes the defect of weak conductivity in metal fluorides, resulting in higher catalytic activity of carbon-supported metal fluorides, enabling more sensitive and efficient catalytic oxidation of nitrite ions.
[0049] Comparative Example 2
[0050] Preparation of carbon-supported metal fluoride CeF3 / C: 1 g of solara gel, 0.15 g of cerium trichloride heptahydrate, 2 g of concentrated polytetrafluoroethylene dispersion, and 5 mL of 10% boric acid solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and then in the center of a tube furnace, where it was incubated at 40 mL / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 500℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cerium fluoride, denoted as CeF3 / C-500.
[0051] CeF3 / C-500 was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the CeF3 working electrode prepared by the method of this invention had a sensitivity of 737.60 μA mM for electrochemical detection of nitrite ions. - 1 cm -2 The detection range is 2.5–1320 μM, and the detection limit is 2.0 μM when the signal / noise ratio is 3 (S / N = 3).
[0052] The results of the detection of nitrite in Comparative Example 2 and Example 1 show that CeF3 / C calcined at 600℃ has higher catalytic activity than CeF3 / C calcined at 500℃.
[0053] Comparative Example 3
[0054] Preparation of carbon-supported metal fluoride CeF3 / C: 1 g of solara gel, 0.15 g of cerium trichloride heptahydrate, 2 g of concentrated polytetrafluoroethylene dispersion, and 5 mL of 10% boric acid solution were uniformly mixed to prepare a gel. The gel was freeze-dried for 48 h to obtain a blocky foam with abundant internal pores. The obtained blocky foam was placed in a ceramic boat and then in the center of a tube furnace, where it was incubated at 40 mL / min. -1 In the Ar gas flow, 5℃min -1 The temperature was raised to 700℃ and held for 2 hours, then allowed to cool naturally. The resulting black substance was ground into powder to obtain carbon-supported cerium fluoride, denoted as CeF3 / C-700.
[0055] CeF3 / C-700 was used for electrochemical nitrite detection: the testing procedure was the same as in Example 1, and the experimental results showed that the CeF3 working electrode prepared by the method of this invention had a sensitivity of 791.30 μA mM for electrochemical detection of nitrite ions. - 1 cm -2 The detection range is 2.2–1400 μM, and the detection limit is 1.7 μM when the signal / noise ratio is 3 (S / N = 3).
[0056] The results of the detection of nitrite in Comparative Example 3 and Example 1 show that CeF3 / C calcined at 600℃ has higher catalytic activity than CeF3 / C calcined at 700℃.
[0057] Anti-interference and stability tests:
[0058] (1) The anti-interference ability of the CeF3 / C working electrode in Example 1 for nitrite ion detection was investigated. After adding 100 μM sodium nitrite solution to 0.1 M phosphate buffer (pH 7.0), the response current of the differential pulse voltammetry curve was recorded. Then, SO42- at a concentration of 500 μM was slowly added. 2- As an interfering substance, the response current of the differential pulse voltammetry curve was recorded. Using the same method, Cl was used... - CO3 2- NH4 + Ca 2+ Experiments were conducted using glucose and other substances as interfering agents, and the response current of the differential pulse voltammetry curve was recorded. The experimental results are as follows: Figure 4As shown, the current response increased significantly after the addition of sodium nitrite solution, but there was no significant change in the current response after the addition of interfering substances, indicating that the CeF3 / C working electrode has good anti-interference ability for electrochemical nitrite detection.
[0059] (2) The stability of the CeF3 / C working electrode in Example 1 for nitrite ion detection was investigated. The current signal for nitrite ion detection of the CeF3 / C working electrode was recorded and analyzed every 10 days. The results are as follows: Figure 5 As shown, the current signal after 60 days was 91.67% ± 2.08% of the initial detection current signal. This indicates that the CeF3 / C working electrode has good signal stability for electrochemical nitrite detection.
[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. An application of a carbon-supported metal fluoride in electrochemical nitrite sensing, characterized in that, The preparation method of the carbon-supported metal fluoride is as follows: Step 1: Add the organic carbon source, metal salt, and concentrated polytetrafluoroethylene dispersion to the solvent and mix evenly to form a sol; The organic carbon source is solara or polyvinyl alcohol; the metal salt is selected from one of cerium salt, iron salt, cobalt salt, calcium salt, magnesium salt, and vanadium salt. Step 2: Freeze-dry the sol to obtain a blocky foam with internal pores; Step 3: Carbonize the block foam by calcining it at 600℃ for 2-4 hours in an inert atmosphere, then grind it after cooling to obtain a black powdery carbon-supported metal fluoride. The carbon-supported metal fluoride is any one of CeF3 / C, FeF3 / C, CoF2 / C, CaF2 / C, MgF2 / C, and VF3 / C; A working electrode is prepared by drop-coating a dispersion of the carbon-supported metal fluoride, ethanol, and Nafion solution onto the surface of a glassy carbon electrode. This working electrode is used for the electrochemical detection of nitrite concentration.
2. The application of carbon-supported metal fluoride as described in claim 1 in electrochemical nitrite sensing, characterized in that, The mass ratio of organic carbon source, metal salt, and polytetrafluoroethylene concentrated dispersion is 1:(0.05~0.3):(1~4).
3. The application of carbon-supported metal fluoride as described in claim 1 in electrochemical nitrite sensing, characterized in that, The solvent is selected from one of boric acid, deionized water, methanol, ethanol, and phenol.
4. The application of carbon-supported metal fluoride as described in claim 1 in electrochemical nitrite sensing, characterized in that, The freeze-drying temperature is -30 to -10°C, and the drying time is 24 to 48 hours.